2000
DOI: 10.1182/blood.v96.12.3712
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous elevation in the serum concentrations of the angiogenic growth factors VEGF and bFGF is an independent predictor of poor prognosis in non-Hodgkin lymphoma: a single-institution study of 200 patients

Abstract: High serum concentrations of vascular endothelial growth factor (S-VEGF) and basic fibroblast growth factor (S-bFGF) are associated with unfavorable clinical characteristics in cancer. The combined effect of S-VEGF and S-bFGF on the survival of 200 patients with non-Hodgkin lymphoma (NHL) was studied. High S-VEGF and S-bFGF at diagnosis were associated with poor survival with the medians, the highest tertiles, or the highest quartiles as the cutoff values. The highest prognostic power was obtained when S-VEGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
80
3
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(95 citation statements)
references
References 42 publications
11
80
3
1
Order By: Relevance
“…(12,13) Moreover, angiogenesis has been associated with adverse outcomes and more aggressive behavior of malignant lymphomas. (14,15) There is substantial inherited genetic variability within VEGF and one of its receptors, VEGF receptor 2 (VEGFR2), including multiple single nucleotide polymorphisms (SNP). The level of VEGF expression varies depending on the presence of a genetic polymorphism.…”
mentioning
confidence: 99%
“…(12,13) Moreover, angiogenesis has been associated with adverse outcomes and more aggressive behavior of malignant lymphomas. (14,15) There is substantial inherited genetic variability within VEGF and one of its receptors, VEGF receptor 2 (VEGFR2), including multiple single nucleotide polymorphisms (SNP). The level of VEGF expression varies depending on the presence of a genetic polymorphism.…”
mentioning
confidence: 99%
“…In a nude mouse model, VEGF increases angiogenesis (4-6), a prerequisite for solid tumor growth beyond a few cubic millimeters in volume (7), and VEGF antibodies inhibit the growth of tumor cell lines in vivo (8)(9)(10). In patients with cancer, high serum VEGF levels serve as markers of progressive or extensive disease (11)(12)(13)(14)(15) and poor prognosis (16)(17)(18). Elevated serum levels of VEGF have also been associated with disease activity in rheumatoid arthritis (19,20), Crohn's disease (21), and ulcerative colitis (21), as well as in angiogenic conditions such as pregnancy (22) and pre-eclampsia (23).…”
mentioning
confidence: 99%
“…Elevated levels of angiogenic growth factors are also associated with an adverse prognosis in patients with non-Hodgkin's lymphoma (NHL). In a single-institution study of 200 patients, levels of serum VEGF were negatively correlated with prognosis [34]. However, the highest prognostic power was observed when VEGF and serum bFGF levels were examined in combination.…”
Section: Elevated Vegf Levels In Hematologic Malignanciesmentioning
confidence: 97%
“…Significantly elevated levels of VEGF are observed in a variety of hematologic malignancies [7,10,34]. A study of 417 patients showed similarly elevated levels of VEGF in patients with AML (n = 115) and advanced MDS (n = 40) compared with controls [7].…”
Section: Elevated Vegf Levels In Hematologic Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation